The African Union challenges of globalization, security, and governance - Makinda, Samuel M. (London Routledge, 2008)
A comprehensive examination of the work of the African Union (AU), with special emphasis on its capacity to meet the challenges of building and sustaining governance institutions and security mechanisms.
Includes bibliographical references (p. [197]-201) and index.
Keywords: African Union